1999
DOI: 10.1037/0033-2909.125.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive integration of language and memory in bilinguals: Semantic representation.

Abstract: Understanding cognitive research on the integration of 2 languages in bilingual memory is difficult because of the different terminology, methodology, analysis, and interpretation strategies that scholars with different backgrounds bring to the research. These studies can be usefully categorized on 2 dimensions: memory for verbal experience versus linguistic knowledge, and systemwise versus pairwise issues. Experimental findings in this area converge on the conclusion that at the word meaning/ conceptual level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
1
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(168 citation statements)
references
References 180 publications
(359 reference statements)
11
150
1
6
Order By: Relevance
“…The above explanatory scenario makes a distinction between the conceptual system and semantic representation by implying that there are separate semantic networks for each language, closely linked and overlapping, so that a conceptual representation may be organized somewhat differently in the two languages. This view is consistent with recent developments (Francis, 1999;Grosjean, 1998;Paradis, 1997;Pavlenko, 1999) in the thinking on the nature of bilingual memory.…”
Section: Discussionsupporting
confidence: 78%
“…The above explanatory scenario makes a distinction between the conceptual system and semantic representation by implying that there are separate semantic networks for each language, closely linked and overlapping, so that a conceptual representation may be organized somewhat differently in the two languages. This view is consistent with recent developments (Francis, 1999;Grosjean, 1998;Paradis, 1997;Pavlenko, 1999) in the thinking on the nature of bilingual memory.…”
Section: Discussionsupporting
confidence: 78%
“…We cannot count languages in mind as first, second, or third languages because they form a unitary system. However, this model is on no firm grounds since L2 users can separate languages in mind (Francis, 1999;Cook 2002). …”
Section: Strategic Readingmentioning
confidence: 99%
“…Testing studied concepts in participants' second language can give relatively unbiased estimates of the conceptual memory strength of pictures and first-language words. Studies of bilingual memory (reviewed by Francis, 1999) have indicated that first-and second-language words refer to a shared conceptual representation. In the present study, English-speaking Swedish students were given surprise memory tests in English after studying lists of Swedish words or pictures.…”
Section: Test Manipulationsmentioning
confidence: 99%